Research Progress on the Effect of Modified Starch on the Quality of Rice Noodles - Xiaofei LIU; Chunyan JIA; Xiang LI; Ming WU; Guang ZHANG; Na ZHANG (Shipin gongye ke-ji)
Rice noodles are one of our traditional staple foods, favored by many consumers. However, issues such as breakage, sticky soup, and poor texture during the cooking process are common. Therefore, understanding the factors affecting the quality of rice noodles is crucial for improving it. Using modified starch is an economical and effective way to enhance rice noodle quality. This paper is based on the formation process of rice noodles, analyzes how starch influences rice noodle quality, specifically the content and fine structure of amylose and amylopectin affect starch gel density, which in turn influences texture and cooking quality. The process of regulating starch structure and composition through modification technology is summarized. Additionally, the mechanisms by which modified starch affects rice noodle quality are summarized, along with future prospects on the development of rice noodles. The goal is to provide scientific references for the production of high-quality rice noodles.